A multidimensional structure of domain-specific problem-solving competencies of electronics technicians for automation technology - Walker, Felix [Verfasser]; Link, Nico [Verfasser]; Nickolaus, Reinhold [Verfasser] (My University, 2016)
"The ASCOT research initiative funded by the Federal Ministry of Education and Research had the objective to measure vocational competencies in high-quality jobs. To adequately assess these it is important to offer authentic situations, similar to real-life (working) situations. Whether domain-specific problem-solving competencies are a unidimensional or a multidimensional construct has far reaching implications in vocational education e.g., regarding valid assessment of performance in the final exam at the end of vocational training. This article deals with the structure of problem-solving competencies of electronics technicians for automation technology at the end of their apprenticeship. Realistic problems with the focus on professional activities such as programming (constructive problem-solving) and troubleshooting a programmable logic controller (analytical problem-solving) were employed to measure domain-specific problem-solving competencies. Based on the results structural equation models were calculated and different models are compared for goodness of fit with consideration to content knowledge and fluid intelligence as predictors." (Authors' abstract, BIBB-Doku)
Keywords: L 3 Lehr-Lern-Forschung; L 6.3.1 Diagnose- & Messinstrumente; L 2.3.2 Handlungs- & problemorientierte Methoden; S 6.2.4 Elektroberufe; Kompetenzdiagnostik; Kompetenzmodell; Fachkompetenz; Problemlösen; Elektroniker für Automatisierungstechnik; Einflussfaktor